Comparison of sagittal lumbar curvature between elite cyclists and non-athletes - Muyor, J. M.; López-Miñarro, P. A.; Alacid, F. (Science & Sports, 2013)
Objective: To compare sagittal lumbar curvature in several positions between elite cyclists and non-athletic subjects. Methods: A total of 60 elite male cyclists and 68 age-matched sedentary controls (mean age: 21.91 ± 2.86 years) participated in the study. Lumbar curvature was measured with a Spinal Mouse® during relaxed standing, maximal trunk flexion in sitting with knees flexed, during a sit-and-reach test, and while sitting on the bicycle with upper-, middle-, and lower handlebar positions. Results: The cyclists exhibited a significantly greater lumbar flexion than non-athletes (P < 0.008) in the postures evaluated. However, no significant differences were found between athletes and non-athletes while standing. On the bicycle, in all three handlebar positions, the cyclists showed a greater lumbar curvature than did the controls (25.33°, 26.02° and 28.47° in cyclists versus 22.27°, 23.04°, and 25.25° in sedentary subjects, respectively). Conclusions: Cycling produces specific adaptations in lumbar curvature when trunk flexion postures are achieved. Cyclists exhibit greater lumbar flexion than non-athletes in maximal trunk flexion and while sitting on the bicycle. However, cycling training does not appear to influence standing lumbar curvature.